2014
DOI: 10.4103/2141-9248.139319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of functional head postures on the dynamic functional occlusal parameters

Abstract: Background:The dentist utilizes supine position during therapeutic procedures, while the patients assumes extended head posture during mastication. It is critical for the restorative dentist to evaluate and understand the possible effect of change in head posture on occlusal contacts. An understanding of the possible effect will help in better restorative rehabilitation.Aim:The aim of the following study is to evaluate the influence of head postures on the dynamic occlusal parameters.Subjects and Methods:Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Two studies reported increased joint position error in TMD groups compared with controls, while two studies found no significant difference between groups. One study 16 reported a significant difference between TMD and control groups when discriminating between mouth opening ranges in relation to a reference block; although overall did not find a significant difference between groups.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Two studies reported increased joint position error in TMD groups compared with controls, while two studies found no significant difference between groups. One study 16 reported a significant difference between TMD and control groups when discriminating between mouth opening ranges in relation to a reference block; although overall did not find a significant difference between groups.…”
Section: Resultsmentioning
confidence: 94%
“…Monteiro et al 1987 59 Higher error in movement accuracy in laterotrusion in TMD group compared to controls (R P = .0005, L P = .0013) between groups. One study 16 reported a significant difference between TMD and control groups when discriminating between mouth opening ranges in relation to a reference block;…”
Section: Proprioceptionmentioning
confidence: 99%
“…The slightly forward inclined head-posture, as instructed to the subjects of the present study sitting on a stool and unsupported by a headrest may also have added to the percentage of AF-bites in comparison to the otherwise analogous T-Scan recording technique employed by Koos et al 22 For ventrally flexed head positions, the axis of rotation of mandible moves forward, according to the “sliding cranium” -phenomenon 26 possibly increasing the likelihood of AF-bites, as has been demonstrated in previous T-Scan studies. 27 , 28 Furthermore, tiny, jaw-closure associated ventral head movements of the unsupported head are coined with protrusion-oriented movements of mandible. 29 During the natural, cyclic chewing movements, the repeated open-close movements would probably not allow sufficient time for the synovial spaces to recuperate and re-inflate between cycles.…”
Section: Discussionmentioning
confidence: 99%
“…30° ventroflexion was included in the study for it is considered as active feeding head position based on the earlier research findings. [ 1 ] The head extends forward by approximately 30° during food consumption; this head posture is known as active feeding posture. It is critical for the dentist to evaluate and understand the possible effect of a change in head posture on occlusal contacts[ 1 ] as generally only upright-erect position is used during restorative procedures, occlusion evaluation, and correction.…”
Section: Discussionmentioning
confidence: 99%
“…These head postures can be divided into an active feeding position posture, upward erect posture and extended head posture. [ 1 2 ] The head extends forward by approximately 30° during food consumption; this head posture is known as active feeding posture. [ 2 ] This posture shifts the mandible and its closure path anteriorly.…”
Section: Introductionmentioning
confidence: 99%